Knowledge, Attitudes, and Practices Regarding Antibiotic Use in RuralBangladesh (The Planet, 2024)
Introduction: Antibiotics have been a cornerstone of modern medicine, yet their misuse has led to the global crisis of antimicrobial resistance (AMR). This study aims to explore the knowledge, attitudes, and practices (KAP) regarding antibiotic use in a rural Bangladeshi community to identify key gaps contributing to this growing issue. Methods & Materials: Conducted at Meghna Upazila Health Complex in Comilla, the cross-sectional survey included a sample size of 60 participants, comprising patients, attendants, and healthcare workers. Result: Findings revealed significant knowledge deficits, with 50% of respondents unaware that antibiotics are ineffective against viral infections and only 30% recognizing the implications of misuse on AMR. Attitudes reflected a normalization of over-the-counter availability and self-medication, with 37% believing antibiotics are necessary for any illness. Practices such as incomplete courses (60%), sharing antibiotics (30%), and improper disposal (40%) further exacerbate resistance risks. Awareness of AMR was low, with only 37% acknowledging it as a serious issue. Conclusion: The study underscores the urgent need for targeted educational interventions, stricter regulatory policies, and community-based awareness campaigns to mitigate antibiotic misuse and combat AMR. These findings provide a foundation for evidence-based strategies tailored to rural settings in Bangladesh, aligning with global efforts to address this critical public health challenge.
Keywords: Antibiotic use; Antimicrobial resistance; Knowledge; Attitudes; Practices; Rural Bangladesh